Facial expressions modulate the gaze orienting effect on sound localization judgement. Issue 2 (7th February 2019) - Liu, Jinmeng; Shi, Yahuan; Whitaker, Lydia; Tian, Yu; Hu, Zhonghua
ABSTRACT: Recent studies have shown that cueing eye gaze can affect the processing of visual information, and this phenomenon is called the gaze-orienting effect (visual-GOE). Emerging evidence has shown that the cueing eye gaze also affects the processing of auditory information (auditory-GOE). However, it is unclear whether the auditory-GOE is modulated by emotion. We conducted three behavioural experiments to investigate whether cueing eye gaze influenced the orientation judgement to a sound, and whether the effect was modulated by facial expressions. The current study set four facial expressions (angry, fearful, happy, and neutral), manipulated the display type of facial expressions, and changed the sequence of gaze and emotional expressions. Participants were required to judge the sound orientation after facial expressions and gaze cues. The results showed that the orientation judgement of sound was influenced by gaze direction in all three experiments, and the orientation judgement of sound was faster when the face was oriented to the target location (congruent trials) than when the face was oriented away from the target location (incongruent trials). The modulation of emotion on auditory-GOE was observed only when gaze shifted followed by facial expression (Exp3); the auditory-GOE was significantly greater for angry faces than for neutral faces. These findings indicate that auditory-GOE as a social phenomenon exists widely, and the effect was modulated by facial expression. Gaze shift before the presentation of emotion was the key influencing factor for the emotional modulation in an auditory target gaze-orienting task. Our findings suggest that the integration of facial expressions and eye gaze was context-dependent.